Soğuk savaş sonrası dönemde Karadeniz Bölgesi ve Türkiye’nin Karadeniz Bölgesi’ne yönelik politikası - Arıdemir, Hakan (My University, 2011)
“Soğuk Savaş Sonrası Dönemde Karadeniz Bölgesi ve Türkiye’nin Karadeniz Bölgesi’ne Yönelik Politikası” başlık doktora tez çalışmasında, Karadeniz Bölgesi’nin siyasi, ekonomik ve coğrafi boyutları ele alınmıştır. Tez, esas itibariyle iki bölümden oluşmuştur. Birinci bölümde, Soğuk Savaş sonrası uluslararası sistemde Karadeniz Bölgesi’nin yeri ve öneminden hareketle tümdengelim yöntemi izlenerek “sistem teorisi” çerçevesinde bir alt sistem olarak Karadeniz Bölgesi’nin sınırları, mevcut dinamikleri ve uluslararası hukuk açısından Karadeniz’in hukuki durumu incelenmiştir. İkinci bölümde ise, Karadeniz Bölgesi’nde etkin olmak isteyen aktörler ve bunların bölgeye yönelik politikaları ele alınmıştır. Bu çerçevede küresel düzeyde politika üreten ABD, AB ve NATO ile bölgesel düzeyde politika üreten Rusya Federasyonu, Ukrayna, Romanya, Bulgaristan, Gürcistan’ın Karadeniz Bölgesi ile sınırlı politikaları değerlendirilmiştir. Aynı bölümde Türkiye’nin Karadeniz Bölgesi’ne yönelik ekonomik istikrarın ve bölgesel güvenliğin sağlanması ve enerji nakil yollarına ilişkin politikaları ele alınmıştır. Halihazırda bölgede mevcut bir dengenin var olduğu, gerek küresel gerekse bölgesel aktörlerin bölgeye yönelik geliştirdikleri politikalarda bu güç dengesinin gözetilmesi gerektiği sonucuna varılmıştır.

In this Doctorial thesis study titled “Blacksea Region in the Post Cold War Period and the Policy of Turkey About Blacksea Region”, the political, economical and geographical dimensions of Black Sea region have been handled. This thesis with regard to the basic consists of two parts. In the first part, by accepting the importance and location of Black sea region as a starting point and adopting the deduction way in this analyse, the borders of Black sea region, the existing dynamics and the juristic position of Black Sea Region in terms of International Law have been analysed, which is seen as a sub-system in accordance with the “System of Theory”. In the second part, that the actors who want to take an active role in the region and their policies about the region have been handled .In this context, The policies of the powers, USA, EU, NATO following a global standing policy and the countries, Russian Confederation, Ukraine, Romania, Bulgaria, and Georgia following a regional standing policy, which are only related to Black Sea Region, have been analysed. In the same part, The policies that Turkey follow for the sake of providing economical stability and the regional security and also its policies about the energy transportation ways have been discussed. It has been inferred that there is an existing balance in the region at present, and the power balance must always be considered in not only the global policies but also the policies that the regional actors follow related to this region.
Keywords: Siyaset ve Yönetim; Soğuk Savaş